2023
DOI: 10.5812/jme-127020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Teacher Evaluation Methods in Medical Education: A Systematic Review

Abstract: Context: Evaluating systems is one of the essential items affecting faculty member performance. Using an appropriate evaluating system is essential for performing different proper roles for faculty members. Objective: This study aimed to systematically review the models, tools, and challenges of evaluating the performance of clinical faculty members. Methods: This systematic review investigated eight international and four national electronic databases in 2019. Descriptive and thematic analyses were done to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Motivation is a critical component of SRL and students intrinsic motivation has been recognized as an significant predictor of academic success, persistence, and determination (Kaplan & Flum, 2009). Intrinsic motivation is malleable and can be influenced by various factors (Brissette & Howes, 2010), including the process of identity formation. Research has found a positive correlation between intrinsic motivation and professional identity, indicating that students with intrinsic motivation are more likely to engage in deep learning and form their professional identity (Wasityastuti et al, 2018).…”
Section: The Mediating Effect Of Intrinsic Motivationmentioning
confidence: 99%
“…Motivation is a critical component of SRL and students intrinsic motivation has been recognized as an significant predictor of academic success, persistence, and determination (Kaplan & Flum, 2009). Intrinsic motivation is malleable and can be influenced by various factors (Brissette & Howes, 2010), including the process of identity formation. Research has found a positive correlation between intrinsic motivation and professional identity, indicating that students with intrinsic motivation are more likely to engage in deep learning and form their professional identity (Wasityastuti et al, 2018).…”
Section: The Mediating Effect Of Intrinsic Motivationmentioning
confidence: 99%